Optimal stopping of semi-stable diffusion processes - Kudžma, R. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. Куджма. Оптимальная остановка полуустойчивых диффузионных процессовR. Kudžma. Pusiau stabiliųjų difuzinių procesų optimalusis stabdymas